Anatomic Differences in the Sagittal Knee Joint Are Associated With ACL Injury: Results From a Skeletally Immature Korean Population. Issue 4 (31st March 2021) - Kwak, Yoon Hae; Nam, Ji-Hoon; Koh, Yong-Gon; Park, Byoung-Kyu; Kang, Kyoung-Tak
Background: Differences in tibiofemoral articular morphology are associated with risks of anterior cruciate ligament (ACL) injury. Purpose: To determine whether bony and cartilaginous morphological characteristics are related to ACL injury in pediatric patients and to investigate any differences according to sex. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 200 skeletally immature Korean patients from a single institution were included in this study; 100 patients had an ACL injury, and 100 had an intact ACL. Condylar morphology and tibial slopes were evaluated and compared between the groups, and differences between sexes were evaluated in the ACL-injured group. Results: The lateral femoral curvature was significantly greater and the lateral and medial tibial curvatures were significantly smaller in the ACL-injured group than in the intact group ( P < .01 for all). In addition, the lateral and medial femoral curvatures as well as the lateral tibial curvature were significantly smaller in female than in male patients ( P < .01 for all). Both the medial and lateral tibial slopes were greater in the ACL-injured versus intact group (medial slope, 5.5° vs 5.0°; lateral slope, 3.0° vs 1.3°, respectively); this difference was statistically significant for lateral tibial slope ( P = .026). No sex-based differences were found for medial or lateral tibial slope. Conclusion: Femoral and tibial curvatures as well as lateral tibial slope were significantly different between the ACL-injured and ACL-intact patients, and the lateral tibial curvature was significantly smaller in female than in male patients. Medial and lateral tibial slopes were not associated with a significant difference in ACL injury between male and female patients.